Cerebrospinal Fluid Fistula by Cold Weapon: Case Report - Barrón, Gema Méndez; Sánchez, Morelos Adolfo García; González, Mireya Fuente; Rodríguez, María Isabel Estrada; García, Giselle Castillo; Rangel, Mario Alberto Zapien; Viloria, Nancy Adelina Velasco; Sedano, Karla Reyes; Celis, Benjamín Reyes; García, Baruj Ricardo Lupio; Salvador, Judá Raquel Hernández; Zenteno, Sergio Fernández; et al. (British Journal of Healthcare and Medical Research, 2023)
Introduction: direct trauma is the origin of many pathologies or diseases, being something so common but to date it is not given importance and the impact that this causes is unknown. A cerebrospinal fluid fistula has been identified or documented in the Surgery department, and is defined as in the communication between the subarachnoid space and the epithelium of the anatomic outlet structure. Objective: is to report a case and review of the medical literature. Clinical case: a 36-year-old male who was attacked by third parties with a sharp instrument in the left posterolateral region of the neck. On the fifth day of his hospital stay, he presented spontaneous, abundant, non-fetid clear fluid leakage through an unquantified surgical wound. It was studied by carrying out a cytochemical protocol and nuclear magnetic resonance; evidencing cerebrospinal fluid leakage due to penetrating trauma to the spine. Discussion: The clinical presentation of a patient with a cerebrospinal fluid fistula is diverse, they can be asymptomatic and go unnoticed, or suffer from orthostatic headache, rhinorrhea, otorrhea, orbitorrhea, or even meningitis. The most successful management is surgical. Conclusion: it is necessary as a surgeon to be aware of knowing that there are no diseases, only patients, and that each patient is different and unique; The possibilities of finding complications, sequelae or consequences that are extremely rare or unknown to some are infinitely possible.